Fenofibrate Improves Liver Function and Reduces the Toxicity of the Bile Acid Pool in Patients With Primary Biliary Cholangitis and Primary Sclerosing Cholangitis Who Are Partial Responders to Ursodiol. Issue 6 (17th July 2020) - Ghonem, Nisanne S.; Auclair, Adam M.; Hemme, Christopher L.; Gallucci, Gina M.; de la Rosa Rodriguez, Randolph; Boyer, James L.; Assis, David N.
Abstract : Cholestatic liver diseases result in the hepatic retention of bile acids, causing subsequent liver toxicity. Peroxisome proliferator‐activated receptor alpha (PPARα) regulates bile acid metabolism. In this retrospective observational study, we assessed the effects of fenofibrate (a PPARα agonist) therapy on bile acid metabolism when given to patients with primary biliary cholangitis (PBC) and primary sclerosing cholangitis (PSC) who have had an incomplete response to Ursodiol monotherapy. When fenofibrate was added to Ursodiol therapy there was a significant reduction and in some cases normalization of serum alkaline phosphatase, alanine aminotransferase, and aspartate aminotransferase abnormalities, as well as pro‐inflammatory cytokines. Combination fenofibrate treatment also reduced 7α‐hydroxy‐4‐cholesten‐3‐one (C4), the bile acid precursor, as well as total, primary, and conjugated bile acids. In addition, principal components analysis and heatmap analysis show that bile acid metabolites trended closer to that of healthy control subjects. These favorable effects of fenofibrate on bile acid metabolism may contribute to its beneficial clinical effects in patients with PBC and PSC experiencing a subtherapeutic response to Ursodiol monotherapy.